BYZANTINE AND SLAVIC POTTERY – IS THERE ANY INFLUENCE? - Krekovic, Eduard (Rei Cretariae Romanae Fautorum Acta, 2024)
For approximately 100 years archaeologists have been finding in the region of Moravia (now the eastern part of the Czech Republic) strange pottery, which seems to be alien there. It is dated to the 9th century AD. During that period the area was the central part of the Moravian kingdom or Magna Moravia. The pottery differs from the local Slavic products in both technology and by shapes. It was therefore considered to be Roman, Avar or Byzantine. However, some scholars considered the possibility of a local origin. A review and summary of the previous opinions on this matter were offered 40 years ago by V. Hrubý. Because fragments of this pottery had been found together with roof tiles in a pottery kiln, he assumed that both articles were produced by Byzantine craftsmen in Moravia. According to him, they came there in AD 863 together with the Byzantine mission of Cyril and Method. However, he did not support his hypothesis by any finds from the territory of the Byzantine Empire, so I decided to reopen this problem.